Valores, estereotipos y capital social como determinantes de las condiciones laborales en Ecuador desde la perspectiva de género - Castillo Alcoser, Paul Elian (2023)
ABSTRACT The objective of this research is to analyze values, stereotypes, and social capital as determinants of labor conditions in Ecuador from a gender perspective for the period 2017-2018. To perform a correct analysis, data from the World Values Survey with focus on Ecuador are used since this instrument considers socioeconomic, social, social capital and religious values. Based on the survey data, once the indicator selection process has been carried out, sections are established that allow a better understanding of the treatment of the information, these sections cover: indicate characterization of all variables, present the hypothesis contrasts for differences associated with employment status, and finally, the choice of econometric estimation based on choice models for ordered variables. The model collaborates in the analysis of the labor situation as it is composed of employment levels ranging from working full time with more than 30 hours a week to situations where unemployment is described as. In the process, ordinal logit and probit estimations are performed, and the Logit Model is selected because it shows lower critical values. The results obtained show that gender is one of the main determinants of employment, and these circumstances women occupy irrelevant positions and are even relegated to domestic work. In addition, among the results, it is corroborated that people who have free time are in higher levels of employment; on the other way, the same effect happens with marital status which is related to the employee's predisposition when entering the work environment. Finally, in our results, it is evident that belonging to women's organizations is not significant in providing a space to establish connections and networks for important positions. Keywords: employment conditions, gender, probit, logit, choice model, choice model, labor, employment.